Prevalent Pest Management Strategies for Grain Aphids: Opportunities and Challenges - Luo, Kun; Zhao, Huiyan; Wang, Xiukang; Kang, Zhensheng (Frontiers in Plant Science, 2022)
Cereal plants in natural ecological systems are often either sequentially or simultaneously attacked by different species of aphids, which significantly decreases the quality and quantity of harvested grain. The severity of the damage is potentially aggravated by microbes associated with the aphids or the coexistence of other fungal pathogens. Although chemical control and the use of cultivars with single-gene-based antibiosis resistance could effectively suppress grain aphid populations, this method has accelerated the development of insecticide resistance and resulted in pest resurgence. Therefore, it is important that effective and environmentally friendly pest management measures to control the damage done by grain aphids to cereals in agricultural ecosystems be developed and promoted. In recent decades, extensive studies have typically focused on further understanding the relationship between crops and aphids, which has greatly contributed to the establishment of sustainable pest management approaches. This review discusses recent advances and challenges related to the control of grain aphids in agricultural production. Current knowledge and ongoing research show that the integration of the large-scale cultivation of aphid-resistant wheat cultivars with agricultural and/or other management practices will be the most prevalent and economically important management strategy for wheat aphid control.